LncRNA CRNDE Promotes ATG4B-Mediated Autophagy and Alleviates the Sensitivity of Sorafenib in Hepatocellular Carcinoma Cells - Chen, Lingxi; Sun, Liangbo; Dai, Xufang; Li, Tao; Yan, Xiaojing; Zhang, Yueting; Xiao, Hanxi; Shen, Xiaodong; Huang, Gang; Xiang, Wei; Zhang, Yan; Tan, Dehong; et al. (Frontiers in Cell and Developmental Biology, 2021)
Autophagy is closely related to the growth and drug resistance of cancer cells, and autophagy related 4B (ATG4B) performs a crucial role in the process of autophagy. The lncRNA (long noncoding RNA) CRNDE (colorectal neoplasia differentially expressed) promotes the progression of hepatocellular carcinoma (HCC), but it is unclear whether the tumor-promoting effect of CRNDE is associated with the regulation of ATG4B and autophagy. Herein, we for the first time demonstrated that CRNDE triggered autophagy via upregulating ATG4B in HCC cells. Mechanistically, CRNDE enhanced the stability of ATG4B mRNA by sequestrating miR-543, leading to the elevation of ATG4B and autophagy in HCC cells. Moreover, sorafenib induced CRNDE and ATG4B as well as autophagy in HCC cells. Knockdown of CRNDE sensitized HCC cells to sorafenib in vitro and in vivo. Collectively, these results reveal that CRNDE drives ATG4B-mediated autophagy, which attenuates the sensitivity of sorafenib in HCC cells, suggesting that the pathway CRNDE/ATG4B/autophagy may be a novel target to develop sensitizing measures of sorafenib in HCC treatment.